Peran Mahasiswa KKN Dan Masyarakat Di Desa Partibi Lama Dalam Pengelolaan Lingkungan Hidup - Darinda Sofia Tanjung; Maria Gresia Marbun; Novi Sitepu; Vivi Haloho; Yusri Fauziah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This research explores the role of KKN students in environmental management in Partibi Lama Village. The aim is to increase public awareness of environmental issues through active collaboration. The method used is qualitative research with a case study approach, involving interviews, observations and group discussions focused on 30-50 village residents. The findings show that the involvement of KKN students has succeeded in increasing community participation in environmental management, creating a cleaner and healthier environment, and strengthening social relations between residents. The implications of this research emphasize the importance of ongoing collaboration between students, village government, and the community to ensure the sustainability of environmental programs.